Teachers' attitude towards blog use in teaching at Malaysian secondary schools - Normie Azura binti Abdul Jamil (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2011)
This study examines Malaysian secondary schoolteachers' attitude towards blog use in teaching. In particular, it seeks to gain insights into the joint effects of perceived ease of use, perceived usefulness, teaching styles, blog competence and teachers' demographics i.e. gender, years of teaching experiences and education levelon teachers attitudes towards blog use. The study adopted a cross sectional survey research approach. Targets respondents were secondary school teachers in Keramat Zone in Wilayah Persekutuan Kuala Lumpur. A total of 700 questionnaires were distributed with 523 used for analysis. The study found that Malaysian teachers generally have a positive attitude towards blog use. Further, teachers' attitude towards blog use in teaching was positively and significantly correlated to perceived usefulness, perceived ease of use, teaching styles and blog competence. Besides, there is no significant difference in teachers' attitude towards blog use in teaching for gender, duration of teaching experiences and education level. In the final analysis, only perceived usefulness, perceived ease of use and teaching styles were found to jointly influence teachers' attitude towards blog use in teaching. Theoretical and practical contributions are also discussed in the dissertation.